Moderasi Islam Ahmad Syafii Maarif (Kontribusinya terhadap Pluralitas Agama di Indonesia) - Saputra, Riki; Putra, Rido; Putri, Endrika Widdia (FIKRAH, 2021)
This study aims to explain the moderation of Islam in Ahmad Syafii Maarif's view which has contributed to the plurality of religions in Indonesia. This research is library research using descriptive-analytical methods and deductive reasoning. In Ahmad Syafii Maarif's view, Islamic moderation is about providing a reinterpretation of religious texts (Islam) with the aim that adherents can understand religion in essence and substance, which will lead to healthier tolerance among religious communities. To realize the moderation of Islam, Ahmad Syafii Maarif made various efforts including; active in various interfaith forums, voicing messages of moderation through writings, also initiated the establishment of the Maarif Institute, institution engaged in the humanitarian and cultural sector. Meanwhile, Ahmad Syafii Maarif's contribution of Islamic moderation to the plurality of religions in Indonesia is that it has sparked the enthusiasm of young people to hold a dialogue in various interfaith forums.